ANTHROPOLOGICAL ASPECTS OF HIGH-TECH FACILITIES OP-ERATION SUPPORT - Olexandr O. Matusevych; Olecsii O. Matusevich (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article, based on the analysis of actual materials, highlights the importance of taking into account the influence of the human factor in occurrence of emergency situations in terms of transport infrastructure. Methodology. The research is based on the interdisciplinary system analysis. It was comprehended how the service technicians of high-tech systems can create latent unsafe conditions that combined with other hazardous activities can cause an emergency and injury. The authors attempt to dramatize the issue in order to find a solution – on the one hand, man is the most crucial part of a complex technological system, on the other hand – he is the most unreliable part of the system, especially in terms of the extreme power of modern vehicles and their speeds. The above situation demonstrates the need for a new level of anthropic comprehension of the high-tech systems in the schematic set "human-system-environment". Originality. The paper analysed the problems and conditions of human factors that allow detecting the causes of technicians’ errors. The authors highlighted proposals for psychocorrective work among the personnel of the facilities. The problem of further development of continuous improvement of the equipment maintenance systems, based on integrated approach taking into account the human factor, is also not overlooked. Conclusion. In the course of understanding the human factor and its influence on the processes, the most urgent tasks are as follows: implementation of new system software, automation of vehicles and development of high production culture based on moral qualities of experts.